Study on properties of hybrid reinforced composite using glass fibers and empty fruit bunch (EFB) fibers - Raodah, Hussin (2016)
The properties enhancement of composite by the combination of synthetic fibers and natural fibers to form the hybrid composite increasing in interest and demand, its lead to increasing the number of studies and research on this hybrid composite. In this research, the hybrid composite of glass fibers and empty fruit bunch fibers is prepared by using Resin Transfer Molding (RTM) instrument. RTM is widely used in industry because it is relatively low cost process. The hybrid composite will be tested on the physical and mechanical properties such as water absorption test, tensile test and impact test. For characterisation, the samples will be characterised using Scanning Electron Microscopy (SEM) and Thermogravimetric Analysis (TGA). The hybrid composite formed have low water absorption, high tensile strength, and high impact energy is required to break the composite samples. Therefore, the hybrid composite formed have good physical and mechanical properties. From the SEM images, the relations between the glass fibers and empty fruit bunch fibers can be seen clearly. Both types of fibers are attached to each other closely by a noticeable structure of polyester resin used for the molding process. The combination of the glass fibers and empty fruit bunch fibers produced the hybrid composite with balanced cost and performance.